Les activités à visée philosophique en maternelle. Histoire française et actualités d’une pratique - Jean-Charles Pettier; Edwige Chirouter (Éducation et Socialisation, 2012)
The documentary It is because the beginning recently revealed in France the existence of activities with philosophic aim in nursery school. Their history is nevertheless more ancient, introduced by G. Tortel within the framework of the pedagogy of initiation after the Second World War. Their current development was made in France according to original and diverse modalities (methods), often ignoring the model introduced by Mr. Lipman in the United States: workshop (studio) of philosophy of Agsas (not interventionist), work of O. Brénifier as occurring (speaking) philosopher, of A. Delsol to help to structure the temporary thought. Educational supports facilitated a distribution adapted to the class, when a work on the youth album, even the development of a specific literature for children, came to support it. The presentation then the scientific analysis of a session realized in nursery school from the reading of an album, allow to seize how the young pupils, thanks to the propping up.